A Fiuméra vonatkozó autonómia terjedelme és intézményei az 1868-as magyar-horvát kiegyezést követően (1868-1883) - Andrási, Dorottya (Közép-Európai Közlemények, 2014)
The regulation of the Compromise between the Hungarian and Croat parties concluded in 1868 aimed to reach back in a large scale to the results of the political-administrative ‘status quo’ before 1848. Provisions of administrative competence on the central tier of administration, i. e. ”corpus separatum” took place pursuant to ‘Pragmatica Sanctio’ referring also to Fiume as a port enjoying privileges, with the exception of the surroundings of Fiume administratively being annexed to Croatia, following the request of the Sabor of Croatia, Slavonia and Dalmatia. Further provisions would have been necessary for the clear delimitation of tasks and scope of the particular administrative matters. This would have been possible to perform on the legislative branch provided and agreement had been concluded between the regularly appointed parliamentary committees. However, this attempt persisted to fail further on. The intermittent status hence legalized, i. e. the ‘provisionary status’ was maintained until as late as the end of the First World War (1870–1918). In the first period, until the 1880s, national and political conflicts and default of standing regulation basically determined development in Fiume and the avail to the local capabilities; this is the time when the foundation was laid down for the development escalating during the 1880s.